Analysis of Factors Associated with Patient Acceptance in the Cancer Navigation Program at Dr. M. Djamil Padang General Hospital in 2024 - Wahyudi, Wawan (PT. Anagata Sembagi Education, 2025)
Cancer remains one of the leading causes of morbidity and mortality in Indonesia, posing challenges in access, timely diagnosis, and continuity of care. To address these gaps, RSUP Dr. M. Djamil Padang implemented a cancer navigation program to guide patients through the treatment process. This study aimed to analyze the factors associated with patient acceptance of the program in 2024. A quantitative cross-sectional design was applied with 100 cancer patients recruited through purposive sampling. Data were collected using a validated structured questionnaire covering socio-demographics, knowledge, family support, healthcare communication, and perceived benefits. Analysis included Chi-square tests and logistic regression with a 95% confidence level. The results showed that 65% of patients accepted the program, while 35% did not. Family support (p=0.001), knowledge level (p=0.021), and healthcare provider communication quality (p=0.004) were significantly associated with acceptance, whereas age, gender, education, and perceived benefits were not. Logistic regression identified family support as the most dominant predictor (OR=3.25), followed by communication quality (OR=2.89) and knowledge (OR=2.10). These findings highlight the importance of social and interpersonal factors in shaping patient engagement. In conclusion, strengthening family involvement, patient education, and communication competencies among healthcare providers is essential to optimize navigation program acceptance, improve continuity of care, and support the national cancer control strategy.